Mothers' personality traits and the climate for creativity they build with their children. (March 2018) - Kwaśniewska, Joanna Maria; Gralewski, Jacek; Witkowska, Eliza Maria; Kostrzewska, Magdalena; Lebuda, Izabela
Highlights: Climate for creativity. Mother. Parent-child relationship. Big Five personality traits. The Climate for Creativity in Parent-Child Relationship Questionnaire. Abstract: Parents' attitudes, behaviors, and traits are significant predictors of their children's creative ability. Not much is known, however, about intentional actions taken by parents to develop and support children's creativity. Based on a literature review and a pilot study (Kwaśniewska & Lebuda, 2017) we have formulated four factors that make up the climate for creativity in a parent-child relationship. To verify the construct empirically, we administered an originally designed questionnaire to mothers in Poland ( N  = 3073). The analysis of results confirms, as predicted, that the following factors contribute to the climate for creativity in the home environment: encouragement to experience novelty and variety, encouragement of nonconformism, support of perseverance in creative efforts, and encouragement to fantasize. Next, we investigated how mothers' Big Five personality traits were linked to particular climate dimensions. Our findings show that openness to experience is the key positive predictor of mothers' activities that shape the climate for creativity in her relationship with the child. The other Big Five traits are associated either positively or negatively with particular dimensions of the climate for creativity.